Peculiarities of FAO Activity in Contemporary Geopolitical Circumstances - N. S. Ivannikov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
This article examines main features of the Food and Agriculture Organization of United Nations diplomatic eﬀorts. Core principles of negotiating activity of organization and its focus are stated. Positive and negative eﬀects inﬂuencing results of the eﬀorts of the organization are considered. Methods of FAO multilateral diplomacy are estimated in the results of the research.